Analysis of the Influence of Digital Marketing and Product Variety on Purchasing Decisions for Beauty Products on the Tokopedia Application - Tampubolon, Rhoni Ilham (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The purpose of this research is to identify and analyze the influence of digital marketing and product variety on purchasing decisions for beauty products on the Tokopedia application among the residents of Tanjung Sari, Medan. This study employs an exploratory research method, with each variable measured using a Likert scale. Data were collected through interviews, questionnaires, and documentation. The population consists of all consumers of PT Tokopedia, totaling 157 individuals. Sampling was conducted using a saturated sampling technique, also known as a census, due to the relatively small population size. Data were processed using SPSS version 23, applying descriptive analysis and hypothesis testing through multiple regression analysis. The findings indicate that (1) digital marketing has a partial influence on purchasing decisions for beauty products on the Tokopedia application; (2) product variety also partially influences purchasing decisions; and (3) digital marketing and product variety simultaneously have a positive and significant effect on purchasing decisions for beauty products on the Tokopedia application among the people of Tanjung Sari, Medan.